2010
DOI: 10.1007/s11665-010-9723-0
|View full text |Cite
|
Sign up to set email alerts
|

Wear Characteristics and Mechanisms of H13 Steel with Various Tempered Structures

Abstract: Wear tests of H13 steel with various tempering microstructures were performed under atmospheric conditions at room temperature (RT), 200°C, and 400°C. The wear characteristics and wear mechanisms of various tempered microstructures of the steel were focused by investigating the structure, morphology, and composition of the worn surfaces. Under atmospheric conditions at RT, 200°C, and 400°C, adhesive wear, mild oxidation wear, and oxidation wear prevailed, respectively. The wear rate at 200°C was substantially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Importantly, due to the formation of a tempered martensite structure, the fracture toughness, fatigue strength and plasticity can be improved. Cui et al [43] reported that wear resistance is proportional to fracture resistance. Therefore, the microstructure after low temperature tempering is beneficial to improve the wear loss, and the slight plastic deformation ability also reduces the CoF.…”
Section: Temperedmentioning
confidence: 99%
“…Importantly, due to the formation of a tempered martensite structure, the fracture toughness, fatigue strength and plasticity can be improved. Cui et al [43] reported that wear resistance is proportional to fracture resistance. Therefore, the microstructure after low temperature tempering is beneficial to improve the wear loss, and the slight plastic deformation ability also reduces the CoF.…”
Section: Temperedmentioning
confidence: 99%
“…Generally, the wear behavior of given steel has a close relationship with its heat-treatment process, hardness, and toughness [10]. Therefore, the researches on the effect of heat-treatment on the wear behavior are of importance to engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the researches on the effect of heat-treatment on the wear behavior are of importance to engineering. Heat treatment can change the mechanical properties of the steel and thus enhance their wear resistance [10][11][12][13][14]. To study the characteristics and the law of the impact wear failure of the test steel, it is tempered at different temperatures to produce various combinations of hardness and toughness.…”
Section: Introductionmentioning
confidence: 99%
“…2 There were many researches performed for the effect of steels and their microstructures and properties, environments, and sliding conditions on the wear behavior and wear resistance. [3][4][5][6][7][8][9][10][11][12][13][14][15] Wang et al [11][12][13][14][15] studied the wear mechanism of H13 steel with different load and ambient temperature. However, the influence of different-hardness counterfaces on the wear of steels has been sparsely reported.…”
Section: Introductionmentioning
confidence: 99%
“…They are reported to prevent the metal-metal adhesion, thus reducing the wear rate. [3][4][5][6][7][8][9][10] Recently, Wang et al [11][12][13][14][15] pointed out that tribo-oxide layer is a predominated factor deciding the behavior of steels, especially at elevated temperature. In the present work, the wear behavior of H13 steels sliding against different-hardness counterface was investigated at various temperatures.…”
Section: Introductionmentioning
confidence: 99%